2021
DOI: 10.1017/s0022029921000194
|View full text |Cite
|
Sign up to set email alerts
|

Investigating cow−calf contact in cow-driven systems: behaviour of the dairy cow and calf

Abstract: Research is needed on how technology can facilitate cow−calf contact (CCC). This research communication describes the behaviour of dairy cow−calf pairs in two cow-driven CCC-systems differing in cows' access to the calves through computer-controlled access gates (smart gates, SG). Specifically, cow traffic through SG when visiting their calves, allogrooming, suckling and cross-suckling, cows' eating and resting behaviour and finally vocal response to separation were assessed. After 3 d in an individual calving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Some research has shown that modern dairy breeds express maternal behaviors toward the newborn calf, including sniffing, licking, and nursing of the calf, especially in the first hours after birth (Jensen, 2011(Jensen, , 2012. However, there is natural individual variation in mothering quality (Edwards and Broom, 1982) and how frequently the cow chooses to visit the calf through an access gate for suckling and allogrooming (Johnsen et al, 2021). It is also possible that some cows may reject their own calf; one study of heifers calving in groups observed 1 of 31 (13%) heifers rejected its calf within 6 h after birth (Illmann and Špinka, 1993).…”
Section: Theme 3: Concern For Required System Changesmentioning
confidence: 99%
“…Some research has shown that modern dairy breeds express maternal behaviors toward the newborn calf, including sniffing, licking, and nursing of the calf, especially in the first hours after birth (Jensen, 2011(Jensen, , 2012. However, there is natural individual variation in mothering quality (Edwards and Broom, 1982) and how frequently the cow chooses to visit the calf through an access gate for suckling and allogrooming (Johnsen et al, 2021). It is also possible that some cows may reject their own calf; one study of heifers calving in groups observed 1 of 31 (13%) heifers rejected its calf within 6 h after birth (Illmann and Špinka, 1993).…”
Section: Theme 3: Concern For Required System Changesmentioning
confidence: 99%
“…Although previous work has assessed the impact of permanent cow-calf separation on cow and calf distress responses [10515], cow-calf rearing systems also require periods of temporary separation, for example when cows go to the milking parlor. Research on temporary separation is limited [16][17] and has focused on motivation and reuniting cows and calves instead of the process of separation. Thus, there is need for work investigating the impact of short-term separation given cows are milked on average twice daily and the potential for a smooth transition to permanent seperation.…”
Section: Introductionmentioning
confidence: 99%
“…The dairy industry and the public are increasingly interested in management systems that allow cow−calf contact (Sirovnik et al, 2020). The cow is highly motivated to visit her calf (Johnsen et al, 2021), indeed will push up to 90 kg to access it (Wenker et al, 2020). There is currently no evidence to indicate early separation is beneficial to cow health (Beaver et al, 2019).…”
Section: Early Dairy Cow-calf Separationmentioning
confidence: 99%